16. ANALISIS POLA PENYELUNDUPAN SENJATA SMALL ARMS AND LIGHT WEAPON (SALW) DI INDONESIA: STUDI KASUS GAM PERIODE 2000-2005 - Panuntun, Mahardhika Damar; Utomo, Tri Cahyo; Farabi, Nadia (Journal of International Relations, 2016)
The purpose of this study was to determine the driving factors behind the smuggling of firearms during the conflict, fire arms smuggling patterns that happened, and the government'sefforts in addressing the issue. In conducting this study, researcher used qualitativeresearch methods in explaining the variables of research to answer the essence ofsmuggling SALW arms during the GAM conflict. This research finds that there are 7factors that encourage the smuggling of weapons by GAM during the conflict in Aceh.Those are, the geographical factor, abuse of authority, a lack of legal mechanisms, lack ofcoordination, a lack of supporting infrastructure, high price of the weapons, and increasingGAM membership.